Quantitative assessment of three Shorea spp for Sungai Menyala Virgin Jungle Reserve, Negeri Sembilan - Hashim, Muhammad Amirul Asyraf (2016)
In Peninsular Malaysia, Virgin Jungle Reserve (VJR) has been established since the 1950’s and are initially known as Permanent Forest Reserve. Due to its status as a Permanent Forest Reserve, the forest has been spared from timber exploitation from the gazetting to the status since 1950. Since then, this forest area changed naturally and this condition is called a Virgin Jungle, meaning it has not been developed or exploited for commercial purposes. This study made use of the abundant tree stands from the family Dipterocarpaceae, genus Shorea present inside the forest reserve.The study was focused on three Shorea species, which all Shorea parvifolia, Shorea acuminata and Shorea leprosula. The objective of this study were to determine the abundance and distribution of these three species and to investigate the difference in basal area and volume of the three Shorea species. The primary data for each species were collected from a belt-transect plot sited at compartment 6 of the forest reserve with covering 2.0 ha. The population density of these three Shorea species, has an average population density for Shorea leprosula of 17.5 trees per hectare, for Shorea parvifolia, 14 trees per hectare and for Shorea acuminata 13.5 trees per hectare. The distribution of trees indicates the adverse characteristic of De iocourt’s factor procedure (reverse J distribution) where stems frequencies increase with the increase in DBH. The growth stage distribution has a growth stage distribution of 3.5% small trees, 37.8% medium trees, 58.7% large trees. From the results for each species in this study, it can be concluded that the study area has a high number of medium sized trees as its main forest structure with Shorea parvifolia being the dominant stand with the biggest number of individuals among the other two but with Shorea leprosula having the biggest volume and basal area, followed by Shorea parvifolia and Shorea acuminata. This study will give a guideline for relevant authority on forest inventory and stand structure determination of Sg.Menyala Permanent Forest Reserve.